"I Spy with My Little Eyes..." The use of video stimulated recall methodology in teacher training – The exploration of aims, goals and methodological characteristics of VSR methodology through systematic literature review. (2019) - Gazdag, Emma; Nagy, Krisztina; Szivák, Judit
Highlights: VSR promotes reflectivity during teacher education. VSR can be used to gain profound insight into novice teachers' developmental paths. It promotes professional growth and commitment to continuous professional development. It is mostly combined with other methods (mixed methods). VSR is useful but time-consuming and energy-intensive. Abstract: The purpose of the study was to discover the advantages of video stimulated recall (VSR) methodology in teacher education. As part of an extensive, systematic literature review researchers therefore focused on the developmental potentials of VSR (as a tool of reflective practice). A reflective attitude has become a fundamental component of the pedagogical sciences, teacher education and teacher evaluation system. Attention is drawn to the fact that despite its labour-intensive and time-consuming nature, VSR can be used to gain profound insight into novice teachers' developmental paths. Incorporating VSR into teacher education could have many benefits in terms of professional growth and commitment to continuous professional development.